Effects of Surface States on the Green Luminescence in ZnO. Issue 10 (9th July 2021) - Hu, Bei-Chen; Zhou, Nan; Zhang, Qing-Yu; Ma, Chun-Yu
Abstract : The origin of green luminescence (GL) band is an issue long‐term pending in the research of ZnO. Herein, three GL bands (GL1, GL2, and GL‐S bands) are unambiguously identified using the single‐crystal samples with and without a SiO x passivation layer and the polycrystal samples annealed in H2 and O2 atmospheres. Solid evidence demonstrates that the GL1 band can be assigned to the optical emissions from the sample inside and the intensity is decreased with the decrease in temperature. The GL2 and GL‐S bands, which correspond to the structureless and structured GL bands of H‐ and O‐annealed samples, respectively, are found to come from the sample surface and enhanced at low temperatures. Excitons or free electrons and holes generated through interband absorption are found to play an important role in exciting both the GL2 and GL‐S bands. For the light with photon energy lower than the bandgap, however, the GL‐S and GL2 bands exhibit different excitation behaviors. The deficiency of oxygen on the sample surface is confirmed to be the reason resulting in the GL2 band and probably also the reason leading to the GL‐S band. Abstract : Green luminescence (GL) band in ZnO comes from the optical emissions of sample inside (GL1) and the surface recombination, i.e., the GL2 in the H‐annealed samples or the GL‐S in the O‐annealed sample.